PERKEMBANGAN ORTODOKSI ISLAM DI PALEMBANG HINGGA AWAL ABAD XX - Aflatun Muchtar; Aristophan Firdaus (Jurnal Ilmu Agama: Mengkaji Doktrin, Pemikiran, dan Fenomena Agama, 2017)
This article will discuss the shape Islam in Palembang until early XX century. This article uses the theory of Islamic classification of Indonesia according to the fiederspiel between Orthodox Islam and Nominal Islam. Orthodox Islam according to fiederspiel (1970) is a group that runs sharia or Islamic tradition firmly based on the understanding of the text. By negating the differences in looking at the elements of local tradition (pure Islam / modernist and traditional Islam) this group has a tendency towards the identity of Islam as the most prominent or embracing it in the political ideology and making it a lifeline. While the nominally Islamic group, is a group that does not place Islam as a primary identity, or as a political ideology. Although the nature of Islamic orthodoxy is more salient but the pragmatism of Islamic political elites can lead to more dynamic political behavior by adjusting to political escalation at the national level.